'A question between empires': the restriction of Japanese immigration in British Columbia and the reassessment of Japan's foreign policy, 1907–1908. Issue 3 (2nd July 2016) - R. Saveliev, Igor
Abstract: Great Britain was the first of the major Powers that revised its unequal treaty with Japan, recognizing the success of Japan's modernization and its growing role in the international arena. However, British Columbia perceived Japanese residents as a threat to 'the British character' of this regions' population profile. After the movement against Japanese residents in British Columbia peaked during the anti-Japanese riots in Vancouver in September of 1907, Canadian Minister of Labor Rodolphe Lemieux headed a diplomatic delegation to Tokyo to negotiate the restriction of Japanese immigration to Canada. The dispatch of this mission revealed some of the complexities in relations between the Colonial and Foreign Offices in London on the one hand and the Dominion's and British Columbian governments on the other. Based on previously unused primary sources, this article will examine the interplay between the policy towards Japanese migrants in the British Dominion of Canada and the British policy towards Japan as a nation.